IDENTIFICATION OF FACTORS RELATED TO MOTIVATION USING VAPORS IN ADOLESCENTS : A LITERATUR REVIEW - Winata, Septian Galuh; Fintriaroqa, Voelda (Universitas Airlangga, 2020)
Introduction: One of the conventional ways to quit smoking is by using e-cigarettes or vapor. Vapor also has bad effects on health if it is used in long term. However, the fact is that vapor is now being misused, especially among teenagers. It is no longer used as a conventional smoking cessation tool, but as a tool to increase popularity. Methods: A literatur review through journal reviews of factors related to motivation to use vapor in adolescents by searching for articles accessed from the internet database such as Pubmed. There were 10 journals that have been filtered by Tex Availability with the following details: Full Text, Article Type: Journal Articles, Publication Date: last 5 years, type: human, language: English, Journal: MIDLINE and Nursing Journal and discusses the factors that influence using e-cigarettes or vapor. Results: Eight of the ten journals that have been obtained explain that the influence of intrinsic factors, namely expectations and interests. It can affect adolescent motivation to use vapor. In terms of the intrinsic factor such as needs, has been proven to have no significant influence for adolescents using vapor. In addition, seven of the ten journals also explained that extrinsic factors, namely the environment also influenced adolescent motivation to use vapor, but extrinsic factors on family drive and rewards did not explain that they could influence adolescent motivation to use vapor. Conclusion: factors related to using vapor in adolescents are motivated by intrinsic factors which are interests and expectations, and by extrinsic factors, namely environment